2013
DOI: 10.1038/jid.2012.490
|View full text |Cite
|
Sign up to set email alerts
|

Rare Pathogenic Variants in IL36RN Underlie a Spectrum of Psoriasis-Associated Pustular Phenotypes

Abstract: Bissell MJ, Hines WC (2011) Why don't we get more cancer? A proposed role of the microenvironment in restraining cancer progression. Nat Med 17:320-9 Brenneisen P, Sies H, Scharffetter-Kochanek K (2002) Ultraviolet-B irradiation and matrix metalloproteinases: from induction via signaling to initial events. Ann N Y Acad Sci 973:31-43 Egeblad M, Werb Z (2002) New functions for the matrix metalloproteinases in cancer progression. Nat Rev Cancer 2:161-74 Fisher GJ, Datta SC, Talwar HS et al. (1996) Molecular basis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
127
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(134 citation statements)
references
References 7 publications
3
127
1
3
Order By: Relevance
“…After the initial reports of missense mutations in IL36RN (the gene coding for IL-36Ra) leading to generalized pustular psoriasis (17,18), several other missense mutations have been identified (38)(39)(40)(41)(42)(43). Altogether, 11 missense mutations of nine different residues have been reported to date (Table I).…”
Section: Il-36ra Mutations Associated With Generalized Pustular Psorimentioning
confidence: 99%
“…After the initial reports of missense mutations in IL36RN (the gene coding for IL-36Ra) leading to generalized pustular psoriasis (17,18), several other missense mutations have been identified (38)(39)(40)(41)(42)(43). Altogether, 11 missense mutations of nine different residues have been reported to date (Table I).…”
Section: Il-36ra Mutations Associated With Generalized Pustular Psorimentioning
confidence: 99%
“…IL-36Ra blocks the proinflammatory cytokines IL-36a/b/g; when IL36RN is mutated, IL-36 signaling is uncontrolled with enhanced production of further proinflammatory cytokines (Onoufriadis et al 2011). However, IL36RN mutations only occur in a minority of patients (Setta-Kaffetzi et al 2013), thus, more genes are likely involved. Interestingly, a de novo mutation in the epidermal NF-kB activator CARD14 (Jordan et al 2012b) has been described to underlay a sporadic case of severe GPP, suggesting that KCs dysfunction is likely to play a predominant role in this disease phenotype.…”
Section: Generalized Pustular Psoriasismentioning
confidence: 99%
“…All rights reserved. [10].These disease alleles are found in both European and Asian populations, and account for approximately 25% of GPP [11], 20% of ACH and 2% of PPP cases [12]. The latter, however, is somewhat controversial, as some studies found no association at all with PPP [13].…”
Section: Accepted Articlementioning
confidence: 99%
“…Another gene involved in GPP, PPP and ACH is AP1S3 [21]. It encodes a subunit of the adaptor protein complex 1 (AP-1), which is an evolutionary conserved heterotetramer that promotes vesicular trafficking between the trans-Golgi network and the endosomes.…”
Section: Accepted Articlementioning
confidence: 99%